Workplace violence against Chinese licensed doctors: a cross-sectional study - Chen, Wenhao; Shi, Jingyu; Xu, Jingyi; Wang, Yue; Wu, Yanbin (Frontiers in Public Health, 2024)
Introduction China has issued and implemented a series of policies aimed at preventing and controlling workplace violence (WPV) against licensed doctors. However, the prevalence of WPV has not been fundamentally curbed. The aim of this study was to present the prevalence of WPV, identify its influencing factors and propose responsive measures. Method The online Chinese Physician Practice Survey was conducted with purposive sampling method among licensed doctors in China from January 2022 to June 2022. Data covered licensed doctors’ sociodemographic characteristics, occupational characteristics, prevalence of WPV, and perception of effective countermeasures. Results A total of 74,305 licensed doctors participated in this study. A total of 44.88% of respondents had experienced WPV, among them, either physical violence only (1.06%) or non-physical violence only (89.91%) or encountered both of them (9.03%). Age, gender, marital status, education level, professional title and registration type were all associated with WPV, being younger, non-married, more educated, and higher professional title are all risk factors for WPV. Male (OR = 1.396, 95CI%: 1.355 to 1.439), clinicians (OR = 1.342,95%CI: 1.177 to 1.529), who were single (OR = 1.174, 95%CI: 1.111 to 1.241), with master’s degree (OR = 2.021, 95%CI: 1.739 to 2.349) and professional title were subsenior (OR = 1.194, 95%CI: 1.125 to 1.267) were most likely to occur WPV. WPV occurred mostly in provincial capitals, public hospitals, primary and community hospitals, and departments of internal medicine, surgery, pediatrics, emergency medicine and mental health. Overall, 44.24% of doctors perceived that strengthening crackdowns on criminal behaviors was the most effective measure to prevent WPV against healthcare staff. Conclusion The frequency of WPV decreased after the implementation of relevant laws and policies. Future efforts should be made to strengthen crackdowns on illegal and criminal activities and to issue specific legal provisions on the prevention and control of WPV against doctors.